Seasonality of Earnings Forecast Errors in the Case of Polish Public Companies - Welc, Jacek (Sezonowość błędów prognoz wyników finansowych polskich spółek giełdowych, 2010)
The earnings forecasts are carefully watched by stock market participants. Analysts, when making those forecasts, exploit a wide range of information. Other approach to earnings forecasting is based solely on corporate historical results and the predictions are made in the mechanical way. However, the empirical evidence points out to low accuracy of earnings forecasts and high seasonality of forecast errors. This stems from the culmination of the assets and liabilities' revaluations at the end of the fiscal year, which results in the increased share of subjectivity in the results reported for the fourth quarter. The paper presents the research on seasonality of the quarterly operating profit forecast errors in the case of Polish public companies. The analysis, conducted for 648 operating profit forecasts in the period between the beginning of 2005 and the end of 2008, showed that the average absolute forecast errors have the highest values in four quarter predictions.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2010; Nr 91, s. 177-185
Keywords: earnings forecasts; analysts forecasts; machanical forecasts; forecast accuracy